Responsible social policy is the key factor of social security (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to the problem of social security, based on the effective social policy. The author on theexamples of foreign and Kazakhstan experience shows measures of social policy, aimed on increasing of welfare,quality and living standard of the population, which, consequently, assist strengthening social security.Key words: social security, social stability, social policy, living standard, social welfare.